2002
DOI: 10.1007/s392-002-8376-8
|View full text |Cite
|
Sign up to set email alerts
|

Sinusknotendysfunktion mit intermittierendem Sinusarrest und AV-junktionaler Ersatzrhythmus als Erstmanifestation eines Phäochromozytoms

Abstract: A 25-year-old male student complained about episodic palpitations, dizziness, nausea and headache 5 years prior to presentation. No otorhinolaryngic, neurologic or gastrointestinal causes were identified. Several ECG recordings revealed sinus node dysfunction with intermittent sinus arrest and AV-nodal escape rhythm. The patient was given a permanent DDD-pacemaker. Six months later, the clinical symptoms were unchanged. During an attack, physical examination revealed paleness, diffuse sweating and an arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…They are due to the secretion of norepinephrine by pheochromocytoma. When betaadrenoceptors are stimulated by excess catecholamine, they can lead to sinus tachycardia, atrial tachyarrhythmia as in our case [5] or even ventricular tachycardias [12], and in rare cases sinus dysfunction [13]. Atrioventricular dissociation was associated with pheochromocytoma in only 2 cases [11].…”
Section: Discussionmentioning
confidence: 64%
“…They are due to the secretion of norepinephrine by pheochromocytoma. When betaadrenoceptors are stimulated by excess catecholamine, they can lead to sinus tachycardia, atrial tachyarrhythmia as in our case [5] or even ventricular tachycardias [12], and in rare cases sinus dysfunction [13]. Atrioventricular dissociation was associated with pheochromocytoma in only 2 cases [11].…”
Section: Discussionmentioning
confidence: 64%
“…5,6 Unfortunately the diagnosis of pheochromocytomaas cause of sinus arrest, atrioventricular dissociation, or supraventricular arrhythmias is frequently delayed, resulting in pacemaker implantation in some cases (as in ours) and even in His bundle ablation for medication resistant arrhythmias. 11,12 After resection of the tumor the arrhythmias resolved in all cases without further need for pacing. In our patient, the urinary concentrations of catecholamines over a 24 hour period were between 5 and 40 times the upper limit of normal, probably reflecting plasma concentrations between 100 and 1000 times the upper limit of normal.…”
Section: Discussionmentioning
confidence: 91%
“…A number of studies have reported that patients with pheochromocytoma developed bradycardia, including sinus arrest or atrioventricular dissociation, during the preoperative period, 3–8 among whom tumor removal preceded arrhythmia resolution. Excess catecholamine secretion increased vagal discharge through the baroreceptor reflex, and adrenergic receptor desensitization have been considered causes of bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…While patients with catecholamine‐secreting tumors usually exhibit tachycardia during the florid phase of their illness, reports have shown that 10% of the patients develop bradycardia 2 . Although a number of studies have shown that some patients with pheochromocytoma present with bradycardia during the preoperative period, 3–8 postoperative bradycardia has remained largely unknown. We present a patient who developed complete atrioventricular dissociation and sinus arrest in the postoperative period after pheochromocytoma resection, which prompted temporary pacemaker implantation.…”
Section: Introductionmentioning
confidence: 99%